INVESTIGATION OF METHODS FOR OBTAINING LARGE-DIAMETER STEEL GRINDING BALLS - Abdrakhmanov, Yermaganbet; Bykov, Petr; Temirtas, Khamit; Kulumbaev, Nurbulat (Journal of Applied Engineering Science, 2024)
The article conducts research on the production of large-diameter steel grinding balls by coquille casting in a garland way, which provides the necessary density of castings. The paper analyzes the material costs for the production of grinding balls ∅ 100 mm by casting and screw rolling, which showed a lower value for the casting method. Also in the work, the calculation of the wall thickness of the coquille was carried out using several methods, on the basis of which the structural elements of the existing coquille installation were selected. The conducted research allowed us to propose a new method of coquille casting balls in a garland way with a central calculated refrigerator, which provides the necessary density of castings.
Keywords: water-cooled coquille, garland casting, central refrigerator, model equipment, special casting box, casting unit